The Science Integration Model in Curriculum Development at State Islamic Higher Education (SIHE) After Changing Into A State Islamic University (SIU) - Syaukani Syaukani; Abd. Mukti; Hasrian Rudi Setiawan (Edukasi Islami : Jurnal Pendidikan Islam, 2023)
This research aimed to identify the concept of science integration at the State Islamic University (SIU) and discovers a model for curriculum development. It was carried out at three SIU, such as Imam Bonjol Padang, Antasari Banjarmasin, and Sultan Maulana Hasanuddin Banten. Data were collected using interviews, observations, and document reviews, and analyzed through the model suggested by Miles and Huberman. A triangulation technique was used to ensure the data are valid. The results showed that 1) the process of integrating science at SIU Iman Bonjol Padang, SIU Antasari Banjarmasin, and SIU Sultan Maulana Hasanuddin Banten is almost similar. This process is carried out by integrating the curriculum into lecture activities, conducting workshops for lecturers, and joint research and community service. 2) Each university uses several models. For instance, SIU Imam Bonjol Padang, Antasari Banjarmasin, and Sultan Maulana Hasanuddin Banten uses the term “sarang lebah” (beehive), “sungai pengetahuan” (source of knowledge), and integration-comparative-diffusion, respectively. The beehive is considered as a paradigm of dialogical interaction integration, while the source of knowledge consists of four integration pillars, dynamic, integration of Islam and nationality, locally based, as well as global perspective.